Molecular Docking and Antimicrobial Screening of Alanine Derived Water-Soluble Cu(II) Complexes - Misbah Shahid (International Journal of Medical Toxicology and Legal Medicine, 2024)
The rise of antibiotic-resistant bacteria reduces the effectiveness of existing antibiotics. This limits treatment options for common infections such as urinary tract infections, pneumonia, and skin infections. To combat antibiotic resistance, there’s an urgent need to develop new antimicrobial agents that can effectively treat resistant infections. To address this problem and its possible solution, aniline and ortho vanillin derived biocompatible and water soluble compounds reported earlier [1] were examined for their potential to inhibit the growth of pathogenic bacteria and control the resulting infection. An in-silico binding investigation was conducted against the potential chemotherapeutic target bacterial DNA (PDB id:1BNA), and the compounds demonstrated significant binding. In vitro Antimicrobial activity of these compounds against pathogenic bacteria Salmonella typhi (NCTC786) and S. aureus (NCIM 5345) at different concentrations. Both the complexes have shown significant results compared to free ligand and with reference to the standard drugs Amoxicillin and erythromycin.